Serum Chemokine CXCL7 as a Potential Novel Biomarker for Obstructive Colorectal Cancer - Li, Longhai; Zhang, Lihua; Zhang, Ting; Qi, Xiaowei; Cheng, Gang; Xia, Lingxia (Frontiers in Oncology, 2021)
Due to the lack of typical symptoms and signs and sensitive indicators for early diagnosis of obstructive colorectal cancer (OCRC), it is critically needed to find new novel biomarkers to ameliorate the management of OCRC patients. In this study, 472 blood samples were collected and measured by enzyme-linked immunosorbent assay (ELISA) to investigate the value of serum chemokine ligand 7 (CXCL7) in diagnosis and prognosis for OCRC patients. The median concentrations of CXCL7 in non-OCRC and OCRC were both higher than that in controls (both P < 0.05). Importantly, the median serum concentration of CXCL7 in OCRC was also higher than that in non-OCRC (P < 0.001). In all OCRC patients, the area under the curve (AUC) of CXCL7 was 0.918 with a sensitivity of 86.54% and a specificity of 81.87%. Similarly, the AUC of CXCL7 was 0.684 when the diagnostic test was performed between OCRC and CRC patients. CXCL7 had a higher AUC than other markers. The concentration of CXCL7 in 40 postoperative OCRC patients was higher than normal people and lower than preoperative patients. The median survival time was 62.00 months and the 5-year overall survival (OS) rate of the patients was 51.80% in all 155 OCRC patients. Multivariate Cox proportional hazard regression model analysis showed that high CXCL7 in serum was independent factors associated with poor OS of OCRC patients (HR = 2.216, P = 0.032). These results demonstrate that serum CXCL7 may be a potential biomarker both in diagnosis and prognosis for OCRC patients.